PSYCHOLOGICAL READINESS OF STUDENTS FOR PROFESSIONAL ACTIVITY IN THE ENVIRONMENT OF INNOVATIVE TECHNOLOGIES - Маковийчук, Кристина; Бевз, Мария; Гончарук, Людмила; Поддубная, Антонина (SWorldJournal, 2021)
The given publication provides the reader with the comprehensive system of scientific and methodological supportion in the process of development of psychological readiness for innovation and competitiveness personality: psycho-organizational technology;